2022
DOI: 10.1083/jcb.202208092
|View full text |Cite
|
Sign up to set email alerts
|

NBR1: The archetypal selective autophagy receptor

Abstract: NBR1 was discovered as an autophagy receptor not long after the first described vertebrate autophagy receptor p62/SQSTM1. Since then, p62 has currently been mentioned in >10,000 papers on PubMed, while NBR1 is mentioned in <350 papers. Nonetheless, evolutionary analysis reveals that NBR1, and likely also selective autophagy, was present already in the last eukaryotic common ancestor (LECA), while p62 appears first in the early Metazoan lineage. Furthermore, yeast-selective autophagy receptors Atg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 108 publications
0
26
0
Order By: Relevance
“…A comparison of these factors in the regulation of ubiquitin-dependent mitophagy suggested that only NDP52 and OPTN play critical roles ( 4 ). In contrast, ubiquitin-dependent pexophagy relies upon NBR1 ( 5 , 6 ). There is also diversity of mechanisms in pathways converging on organelle turnover.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of these factors in the regulation of ubiquitin-dependent mitophagy suggested that only NDP52 and OPTN play critical roles ( 4 ). In contrast, ubiquitin-dependent pexophagy relies upon NBR1 ( 5 , 6 ). There is also diversity of mechanisms in pathways converging on organelle turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Ezurpimtrostat treatment led to decreased NBR1 protein expression in cancer cells. In addition to the NBR1 mRNA expression found in most cancers, it was associated with low cancer specificity (35,36). NBR1 overexpression increased the proliferation of renal cancer cells in vitro (37) and promoted tumor metastasis in a breast cancer mouse model (38).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Protein aggregates also represent ancestral noxious objects dealt with already in prokaryotes through disaggregating enzymes ( 41 ) and may have been among the first targets of this evolving selectiveness, as witnessed by the presence of an ancestral form of NBR1 in the LECA ( 42 ).…”
Section: The Evolution Of Autophagymentioning
confidence: 99%